Intercultural sensitivity in the online multicultural community: Indonesian students' experiences - Puspitasari, Febi (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2023)
The online social network facilitates excessive opportunities for intercultural communication in the online multicultural community. Occasionally, intercultural communication possibly results in misunderstanding, confusion, or stereotypes. Intercultural sensitivity, therefore, is necessary to respond to probable issues in online intercultural communication based on Indonesian students' experiences. This narrative study portrayed the development of intercultural sensitivity in the online multicultural setting. The data were compiled from narrative reports and recordings and then analyzed based on Hunter's analysis of the narrative. It reveals the development of intercultural sensitivity in the themes of 1) embracing a phonemic variation of English, 2) developing mutual strategies to understand the language, 3) celebrating small similarities, and 4) self-control to listen respectfully. The findings are primarily meant for intercultural education. The study also suggests the use of an authentic intercultural setting for English language learners to develop their intercultural sensitivity and bring the discussions after practice in the classroom.